Productivity, Real Wages, and Economic Growth - Smithies, Arthur (Quarterly Journal of Economics, 1960)
I. Facts and theory, 189. — II. Elements of the model, 192. — III. The operation of the model: nonmathematical, 193. — IV. Capital requirements, 197. — V. Mathematical recapitulation, 198. — VI. A numerical illustration, 204.